Ethnobotany of stinging nettle (Urtica simensis Hochst. ex. A. Rich.) in the Oromia region of central and southeastern highlands of Ethiopia - Tigist Tadesse Shonte; Kebede Woldetsadik (CABI Agriculture and Bioscience)
Abstract Background Stinging nettle, Urtica simensis, has a wide range of distribution in the highlands of Ethiopia with untapped potential for a sustainable supply of healthy and nutritious food. This study was conducted to document ethnobotanical uses of U. simensis and the associated traditional knowledge of the indigenous people and to identify the factors limiting harvesting and utilization of stinging nettle in North Shewa (R4), Bale and Arsi zones of the Oromia region, central and southeastern highlands of Ethiopia. Methods Thirteen districts were purposively selected from the three zones and a total of 130 respondents were sampled, with consideration of gender, age, occupation, and wealth status. Data were collected using semistructured interviews, tour-guided field observations, and focus group discussions. IBM SPSS Statistical software package was used to analyze ethnobotanical data. Results Pearson’s chi-square analysis showed that there is a significant association (P < 0.05) between zones and districts in the ethnobotanical knowledge of use categories. Stinging nettle plants have an average use value index of 0.91 with a central role (FL = 44.8%) as a source of food and fodder. Cultural norms and values followed by lack of knowledge and stinginess were the main limiting factor for harvesting and consumption of U. simensis. Cultural norms and values showed significantly higher correlations with the various uses of U. simensis (r2 = 0.931, p < 0.001) indicating the stigma related to stinging nettle being associated as poor man food or famine food were probably a major limiting factor for the utilization of U. simensis. Conclusions Future strategic policies should consider U. simensis as a source of food and fodder to fight food insecurity and improve the wellbeing of society. There is a need for local level and countrywide awareness creation, domestication, and future research on value addition and processing for effective utilization of the plant.